2016
DOI: 10.18632/oncotarget.9526
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization by the investigational NEDD8-activating enzyme inhibitor MLN4924 (pevonedistat) in hormone-resistant prostate cancer cells

Abstract: Salvage radiotherapy (SRT) is the first-line treatment for prostate cancer patients with biochemical recurrence following radical prostatectomy, and new specific radiosensitizers are in urgent need to enhance SRT effect. MLN4924 (also known as Pevonedistat), a specific inhibitor of NEDD8-activating enzyme, has recently entered phase I/II clinical trials in several malignancies. By inhibiting cullin neddylation, MLN4924 inactivates Cullin-RING ligases (CRL), which have been validated as an attractive radiosensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The present study demonstrated that MLN4924 could induce G 2 cell cycle arrest in ESCC cells. At the same time, MLN4924 significantly enhanced the protein stability of p21, p27 and Wee1, which is in accordance with previous studies (9,15), where they indicate that all of the 3 proteins serve an important function in MLN4924-induced G 2 cell cycle arrest (23).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrated that MLN4924 could induce G 2 cell cycle arrest in ESCC cells. At the same time, MLN4924 significantly enhanced the protein stability of p21, p27 and Wee1, which is in accordance with previous studies (9,15), where they indicate that all of the 3 proteins serve an important function in MLN4924-induced G 2 cell cycle arrest (23).…”
Section: Discussionsupporting
confidence: 92%
“…Previously, MLN4924 exhibited attractive pharmacodynamic effects in phase I studies in patients with advanced solid tumors, relapsed/refractory lymphoma and metastatic melanoma for its tolerable safety profile (17)(18)(19). MLN4924 may function as a novel chemosensitizer or radiosensitizer in multiple types of cancer (20)(21)(22)(23)(24). These results indicate that targeting the neddylation pathway may represent an attractive anticancer strategy, either alone or in combination with other therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Many RB therapies induce DNA damage 1 and MLN4924 synergizes with DNA damaging agents 30 , including radiation [31][32][33] . Our in vivo study showed IVT MLN4924 was effective, however in the schedule used we did not observe any complete responses (CR), therefore residual tumor cells would likely regrow.…”
Section: Discussionmentioning
confidence: 99%
“…al. that silencing of UBC12, the NEDD8 E2 enzyme, sensitizes prostate cancer cells to radiation . In 2009, a small‐molecule inhibitor called MLN4924 was developed to specifically target the neddylation E1 enzyme, NAE, potently blocking cullin neddylation and activation .…”
Section: Ring E3 Ligasesmentioning
confidence: 99%